Creating research impact through the productive interactions of an individual: an example from South African research on maritime piracy. Issue 2 (28th January 2019) - Boshoff, Nelius; Sefatsa, Mpho
Abstract: This study applied the 'productive interactions' approach of research impact assessment to the case of maritime piracy research in South Africa. The focus was on the stakeholder interactions associated with the doctoral work and related activities of an individual researcher. A set of documents—provided by the researcher as evidence of potential impact—was coded systematically in terms of the direct and indirect interactions reflected and whether those interactions were productive. Evidence of either research uptake or research use was taken to imply a productive interaction. The coding generated eleven instances of productive interactions, presented in the form of a contribution narrative. Additional information for contextualization, obtained from interviews with the researcher and one of the stakeholders, was also considered. The study highlights the role of research in relation to an expert's productive interactions and comments on the feasibility of self-documentation as a method for data collection when constructing an account of contribution. A framework that addresses the lack of focus on the broader effects of productive interactions is also presented, for consideration in future studies of the impact of individual researchers.